Gender, sex, and sexuality among contemporary youth : Generation Sex - Claster, Patricia Neff; Blair, Sampson Lee (Sociological studies of children and youth, 2017)
This volume examines the evolving norms concerning sex, gender, and sexuality in the lives of children and adolescents addressing topics such as: the development of gender identity, sexual behavior among youth, LGBT youth, transgendered youth, parental and peer influences upon the development of gender and gender identity and dating violence.